PERUBAHAN NILAI DAN FILOSOFIS BUSANA KEBAYA DI JAWA TENGAH - santoso, ratna endah; widyastuti, Theresia; Sakuntalawati, LV Ratna Devi; Josef, Adji Isworo; Affanti, Tiwi Bina (Institut Seni Indoensia Surakarta, 2019)
The Javanese who live in the Central Java region are known for their cultural strength. This can be seen from how they uphold the heritage traditions of their ancestors. Besides that, Central Javanese people are easily known through their typical costume. Kebaya and its equipment from head to toe, it is said that initially only used by the royal community had a quite interesting value and philosophy. For decades kebaya as part of history, experienced various changes in line with the era that continues to run. The most important thing is that kebaya is no longer an everyday outfit like in the past.This research paper uses qualitative research using a cultural approach. This study aims to find out (1) changes in values and philosophies such as what happened to kebaya clothing specifically used in the Central Java region; (2) whether today's kebaya can still be called traditional clothing, especially with various changes caused by current conditions.